TARIK ULUR KOMPETENSI ABSOLUT LEMBAGA ARBITRASE (Kajian Terhadap Prinsip Niet van Openbaar Orde dan Pacta Sunt Servanda Dalam Klausul Arbitrase) - Ayu Atika Dewi (Faculty of Law, Maranatha Christian University, 2018)
Arbitration is an institution of dispute settlement based on arbitration agreements. An arbitration agreement may be an arbitration clause incorporated by a standing agreement or an arbitral agreement independent of its principal agreement. Based on the arbitration agreement, there are two principles named Niet van Openbaar Order and Pacta Sunt Servanda. Based on the principle of the arbitration clause of the Niet van Openbaar Order, the arbitration clause does not necessarily provide the competence of the arbitration body to resolve the dispute under arbitration agreements. Instead the principle of clause is Pacta Sunt Servanda provides absolute competence for the arbitration body to resolve the dispute. The existence of these two principles leads to a lack of interpretation of the absolute competence of arbitration among law practitioners. This study aims to find out how exactly the competence of arbitration institutions in settling disputes that have been bound arbitration agreement is based on the duality principle of Niet van Openbaar Order and Pacta Sunt Servanda arbitration clause in Indonesian law. The results of the study explained that the legislation in the legal system of Indonesia as stipulated in Law no. 30 of 1999 has expressly stated that absolute competence for arbitration institution as the institution of dispute settlement which is bound by arbitration agreement. Therefore, the legal practitioners should return to the legal norm in order not to happen again the tug of competence to adjudicate disputes between the arbitration institution and the court institution. With this it is expected that the legal certainty in the arbitration order can be enforced.